COMPARATIVE ERROR ANALYSIS IN ENGLISH WRITING BY FIRST, SECOND, AND THIRD YEAR STUDNETS OF ENGLISH DEPARTMENT OF FACULTY OF EDUCATION AT CHAMPASACK UNIVERSITY - Sychandone, Nokthavivanh (Universitas Muhammadiyah Surakarta, 2016)
levels. To investigate the error types, the frequency of error types, the similarities and difference of errors and the last to find the error sources that occur in first, second and third year learners. Error analysis is one type of linguistic study and it focuses on learnersâ error making. The linguistic category and surface strategy taxonomy are used to find out the types of error. The analysis the phenomenon based on Brown (1980) namely, error identification, error classification, Error description and error explanation. The data from studentsâ writing products, 54 pieces in three levels andthe total errors are 571 erroneous sentences. There are two types of errors, namely lexical errors and syntactical errors; eight error categories and twenty-seven error cases. The second year learners made the most error 263 errors or 46, 05% whilefirst year learners produced 229 errors or 40, 10% and third year learners made 79 errors or 13, 83%. There are similarity in errors types, five similar categories and five error cases, but there are three different error categories and eighteen error cases. The main error sources, learners had lack knowledge of English grammatical rule. The overgeneralization (265 errors or 46, 40%) influences learnersâ error, language transfer (199 errors or 34, 85%) still interfere learnersâ acquisition and simplification (107 errors or 18, 73%) is one factor that effect learnersâ errors.